2007
DOI: 10.1109/tvt.2007.900525
|View full text |Cite
|
Sign up to set email alerts
|

A Service-Agent-Based Roaming Architecture for WLAN/Cellular Integrated Networks

Abstract: Abstract-In this paper, an agent-based integrated service model for wireless local area network (WLAN)/cellular networks and the relevant authentication and event tracking for billing support schemes are proposed. The service model does not require inefficient peer-to-peer roaming agreements to provide seamless user roaming between the WLAN hotspots and the cellular networks, which are operated by independent wireless network service providers. The proposed authentication and event-tracking schemes take the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…On the other hand, localized authentication, which aims at localizing the authentication process between the tWISP and MUs without contacting the hWISP and the RB, created a new paradigm toward shortening the authentication delay and reducing the load on the RB [22]. In [23] and [24], it is suggested that a local AAA server be used as a buffer for caching the security contexts for each active MU. This scheme can greatly improve the performance since an MU requesting for handoff needs to communicate with the home AAA server only for once, and then, the subsequent authentication procedure can be performed at a local AAA server.…”
Section: Related Workmentioning
confidence: 99%
“…On the other hand, localized authentication, which aims at localizing the authentication process between the tWISP and MUs without contacting the hWISP and the RB, created a new paradigm toward shortening the authentication delay and reducing the load on the RB [22]. In [23] and [24], it is suggested that a local AAA server be used as a buffer for caching the security contexts for each active MU. This scheme can greatly improve the performance since an MU requesting for handoff needs to communicate with the home AAA server only for once, and then, the subsequent authentication procedure can be performed at a local AAA server.…”
Section: Related Workmentioning
confidence: 99%
“…In [13], [14], it is suggested to make use of a local AAA server as a buffer for caching the security contexts for each active MU. This scheme can greatly improve the performance since an MU requesting for handoff needs to communicate with the home AAA server only for once and then the subsequent authentication procedure can be performed at a local AAA server.…”
Section: A Related Workmentioning
confidence: 99%
“…Our work is different from (Long et al, 2004;Baek et al, 2006;Shi et al, 2007) in the sense that an embedded two-factor authentication mechanism is implemented to determine whether a roaming MU is authentic without any intervention of the MU's home network as well as exchanging the authentication key in case the MU is authentic. A two-factor authentication mechanism is considered as a much stronger authentication method than the previously reported schemes since two independent authentication methods are adopted to ensure a MU to be a legitimate user, such as 'something you know' as one, and 'something you have' or 'something you are' as the other.…”
mentioning
confidence: 95%
“…In addition to providing mutual authentication, the authors demonstrated that the protocol can defend various threats such as replay attack, man-in-the-middle attack, and key exposure. Shi et al (2007) realised localised authentication by using ticket, which is secrecy kept by MSs and APs after their first time authentication.…”
mentioning
confidence: 99%